Some Generalized Difference Sequence Spaces Defined by a Sequence of Moduli in n-Normed Spaces. (26th May 2015) - Alotaibi, Abdullah; Raj, Kuldip; Mohiuddine, S. A.
Abstract : We introduce some new generalized difference sequence spaces by means of ideal convergence, infinite matrix, and a sequence of modulus functions overn -normed spaces. We also make an effort to study several properties relevant to topological, algebraic, and inclusion relations between these spaces.